The Use of Zeolit and Activated Carbon on Packing System of Corydoras aenus - Supriyono, E.; Supendi, E.; Nirmala, K. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
Problem frequently found by Indonesian exporter in sending ornamental fish including Corydoras aenus to overseas is the low survival rate that caused by decrease in water quality during transportation. Suitable and efficient packing technology is very needed to send live fish for long time transportation. Two third of packing plastic volume was filled by oxygen, and Corydoras aenus 20 fish/pack. Packing plastic was placed into styrofoam and ice was added to maintain at low temperature. Zeolit and activated carbon was cover up by cloth and then placed into the pack. Dosage treatment of zeolit and activated carbon was 20 gram zeolit, 15 gram zeolit and 5 gram activated carbon, 10 gram zeolit and 10 gram activated carbon, 5 gram zeolit and 15 gram activated carbon, 20 gram activated carbon, and no added zeolit and no activated carbon as control. Fish condition was observed every 6 hours, while water quality measurement was performed every 24 hours for 120 hours. The results of study showed that adding 20 gram zeolit without activated carbon in closed packing system of Corydoras aenus in 20oC could maintained in lower concentration of total nitrogen ammonia and unionized ammonia (NH3), reached of 7.83±0.13 mg/l and 0.046±0.003 mg/l, respectively. The level of total nitrogen ammonia and unionized ammonia were relatively lower compared to mix of zeolit and activated carbon, and only activated carbon. Survival rate of fish by this treatment was 100%, higher than other treatment (85-95%). Keywords: zeolit, activated carbon, packing, Corydoras ABSTRAK Permasalahan yang sering dihadapi oleh para eksportir Indonesia dalam pengiriman ikan hias termasuk Corydoras aenus ke luar negeri adalah rendahnya survival rate diantaranya disebabkan oleh kualitas air yang memburuk selama pengangkutan. Teknologi pengepakan yang tepat dan efisien sangat dibutuhkan dalam rangka pengiriman ikan hidup untuk tempat tujuan yang membutuhkan waktu lama. Kantong pengepakan diisi Corydoras aenus 20 ekor/kantong. Dua per tiga bagian kantong diisi oksigen. Kantong dimasukkan ke dalam styrofoam dan ditambahkan es batu untuk menjaga suhu tetap rendah. Zeolit dan karbon aktif dibungkus kain dan dimasukan ke dalam kantong. Perlakuan dosis zeolit dan karbon aktif adalah 20 gram zeolit, 15 gram zeolit dan 5 gram karbon aktif, 10 gram zeolit dan 10 gram karbon aktif, 5 gram zeolit dan 15 gram karbon aktif, 20 gram karbon aktif, dan tanpa zeolit dan tanpa karbon aktif sebagai kontrol. Pengamatan kondisi ikan dilakukan setiap 6 jam, sementara pengukuran kualitas air dilakukan setiap 24 jam hingga jam ke-120. Hasil penelitian menunjukkan bahwa pemberian 20 gram zeolit tanpa Carbon aktif pada pengepakan tertutup ikan Corydoras aenus dengan suhu sekitar 20oC mampu menekan kenaikan kadar total amonia nitrogen dan kadar amonia tak terionisasi (NH3) masing-masing mencapai tingkat 7,83±0,13 mg/l dan 0,046±0,003 mg/l. Konsentrasi tersebut relatif lebih rendah bila dibandingkan dengan penggunaan campuran zeolit dan arang aktif maupun arang aktif saja. Tingkat kelangsungan hidup yang dicapai oleh sistem pengepakan menggunakan 20 gram zeolit mencapai 100% yang juga lebih baik dibandingkan dengan perlakuan lain yang hanya mencapai 85-95%. Kata kunci: zeolit, karbon aktif, pengepakan, Corydoras